2012
DOI: 10.1590/s0100-879x2012007500041
|View full text |Cite
|
Sign up to set email alerts
|

Neural regulation of the stress response: glucocorticoid feedback mechanisms

Abstract: The mammalian stress response is an integrated physiological and psychological reaction to real or perceived adversity. Glucocorticoids are an important component of this response, acting to redistribute energy resources to both optimize survival in the face of challenge and to restore homeostasis after the immediate challenge has subsided. Release of glucocorticoids is mediated by the hypothalamo-pituitary-adrenal (HPA) axis, driven by a neural signal originating in the paraventricular nucleus (PVN). Stress l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
182
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(190 citation statements)
references
References 45 publications
1
182
0
7
Order By: Relevance
“…Both receptors have two modes of action, a rapid non-genomic mode and a slow genomic mode, mediated by receptors residing at the membrane or in the cytoplasm, respectively, as demonstrated mostly in rodents or in vitro (Joëls et al, 2012). Whereas the slow genomic effects promote reinstalling homeostasis in humans and rodents (presumably GR-mediated, Henckens et al, 2011;Herman et al, 2012), rapid non-genomic (MR-mediated) effects seem to enhance catecholaminergic effects within minutes, for example, by enhancing excitability of the amygdala in vitro (Karst et al, 2010). Studies investigating emotional memories in rodents have already demonstrated that both stress-systems have synergistic effects in the amygdala (eg, Roozendaal et al, 2006).…”
Section: Effects Of Mineralocorticoid Receptor Blocking In Humans S Vmentioning
confidence: 99%
“…Both receptors have two modes of action, a rapid non-genomic mode and a slow genomic mode, mediated by receptors residing at the membrane or in the cytoplasm, respectively, as demonstrated mostly in rodents or in vitro (Joëls et al, 2012). Whereas the slow genomic effects promote reinstalling homeostasis in humans and rodents (presumably GR-mediated, Henckens et al, 2011;Herman et al, 2012), rapid non-genomic (MR-mediated) effects seem to enhance catecholaminergic effects within minutes, for example, by enhancing excitability of the amygdala in vitro (Karst et al, 2010). Studies investigating emotional memories in rodents have already demonstrated that both stress-systems have synergistic effects in the amygdala (eg, Roozendaal et al, 2006).…”
Section: Effects Of Mineralocorticoid Receptor Blocking In Humans S Vmentioning
confidence: 99%
“…Increased activity in the sympathetic-adrenal system involves a rapid release of adrenaline and noradrenaline from adrenal chromaffin cells and sympathetic nerve terminals, respectively (7). Moreover, stress-induced activation of the HPA axis involves the synthesis and secretion of glucocorticoids (cortisol in humans and corticosterone in most rodents) from the adrenal cortex (8). Both animal and human studies have shown that these stress hormones have profound effects on cognition by acting on specific brain regions involved in the processing of emotional stimuli (1,(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…An excessive concentration of glucocorticoids can have deleterious effects on the developing organism [41,42] and it could permanently affect the expression of Glucocorticoid receptors [43] which are vital for the negative feedback circuit that inhibits Glucocorticoid secretion [44].…”
Section: The Hpa Axismentioning
confidence: 99%